In vivo synthesis of bacterial amyloid curli contributes to joint inflammation during S. Typhimurium infection. - Amanda L Miller; J Alex Pasternak; Nicole J Medeiros; Lauren K Nicastro; Sarah A Tursi; Elizabeth G Hansen; Ryan Krochak; Akosiererem S Sokaribo; Keith D MacKenzie; Melissa B Palmer; Dakoda J Herman; Nikole L Watson; et al. (PLoS Pathogens, 2020)
Reactive arthritis, an autoimmune disorder, occurs following gastrointestinal infection with invasive enteric pathogens, such as Salmonella enterica. Curli, an extracellular, bacterial amyloid with cross beta-sheet structure can trigger inflammatory responses by stimulating pattern recognition receptors. Here we show that S. Typhimurium produces curli amyloids in the cecum and colon of mice after natural oral infection, in both acute and chronic infection models. Production of curli was associated with an increase in anti-dsDNA autoantibodies and joint inflammation in infected mice. The negative impacts on the host appeared to be dependent on invasive systemic exposure of curli to immune cells. We hypothesize that in vivo synthesis of curli contributes to known complications of enteric infections and suggest that cross-seeding interactions can occur between pathogen-produced amyloids and amyloidogenic proteins of the host.